Enhancing Electrochemical Properties of BSCF-Based Cathode Composite Through Catalyst Addition for Low-Temperature Solid Oxide Fuel Cells - Yusop, Umira Asyikin; Nurul Farhana Abdul Rahman; Wan Nor Anasuhah Wan Yusoff; Baharuddin, Nurul Akidah; Tan Kang Huai; Jarot Raharjo; Abd.Rahman, Hamimah (International Journal of Integrated Engineering, 2026)
Solid oxide fuel cells (SOFCs) are promising alternative energy sources; however, their commercialisation is hindered by the requirement of high operating temperatures. The development of low-temperature SOFCs (LT-SOFCs) offers a potential solution to mitigate this limitation, with barium strontium cobalt ferrite (BSCF) emerging as a promising mixed ionic and electronic conductor (MIEC) material for cathode applications. Nevertheless, the advancement of BSCF-based cathodes necessitates further enhancements in both conductivity and stability to achieve optimal performance. This study investigates the incorporation of 1, 3, and 5 wt.% argentum (Ag) as a catalyst material into a BSCF-samarium doped ceria (BSCF-SDC) composite cathode, with the objective of improving its chemical, physical, thermal, and electrochemical properties for LT-SOFC operation within the temperature range of 400 - 600°C. The particle size increases with the increment of Ag addition, enhancing the triple-phase boundary (TPB) length at the cathode-electrolyte interface. The composite cathodes exhibited optimised porosity ranging from 35.34% to 36.45%, falling within a sufficient porosity of 20% - 40% for SOFC cathode components. The TEC analysis revealed improved compatibility with the electrolyte as Ag content increased, with BS-Ag5% showing the lowest TEC mismatch (2.1%), indicating enhanced thermal stability. The electrochemical performance, ASR, also increased with higher Ag content while maintaining a consistent trend across operating temperatures. By this outcome, the presence of secondary phases, such as BaFe₂O₄ and CeO₂, did not adversely affect cell performance; instead, they may have contributed to catalytic activity and structural stability. The study concludes that BS-Ag composite cathodes exhibit significant potential for LT-SOFC cathode materials.